Structural and dielectric properties of the fluorite-type LaxCe1−xO2−δ ceramics. (14th November 2017) - Singh, Kushal; Kumar, Kundan; Nayak, Sanjib; Joshi, Deep Chandra; Alom, Mir Motakabbir; Thota, Subhash; Chowdhury, Anirban
Abstract: High density (95–97%) La x C e 1 − x O 2 − δ ( x = 0.1, 0.2 ) ceramics were tested for structural and dielectric properties. Dense microstructure and controlled phase-purity were obtained for all the L a 3 + -doped samples. A surprising three-fold increase was noticed in the frequency dependent dielectric permittivity ϵ r ( f ) behavior for the L a 0.2 C e 0.8 O 2 − δ ceramic, associated with the space-charge polarization at grain boundaries or inhomogeneous microstructure of the ceramic. High resistivity (̃10 8 Ωm) at room temperature was noticed for the ceramics (at 100 Hz). Hopping of electrons within the oxygen vacancies were noted as the main transport mechanism; strong localization of charge carriers were noticed at high frequencies. The temperature dependent ac-resistivity analysis ρ a c (T) provides strong evidence for Mott's variable range hopping process of charge carriers, between the localized states with an average hopping length of RH of 3 nm and hopping energy of WH of 0.67 eV. Moreover, the effect of grains and grain boundaries on the correlation between ac-conductivity σ a c and angular-frequency ω has been discussed in detail.